Using Slow-Paced Breathing to Foster Endurance, Well-Being, and Sleep Quality in Athletes During the COVID-19 Pandemic - Borges, Uirassu; Lobinger, Babett; Javelle, Florian; Watson, Matthew; Mosley, Emma; Laborde, Sylvain (Frontiers in Psychology, 2021)
The coronavirus disease 2019 (Covid-19) has been causing major disruptions in the sporting world. Negative physiological and psychological effects on athletes have been reported, such as respiratory issues and increased stress. Therefore, it is timely to support this population by presenting cost-effective and accessible intervention techniques to reduce this impact. Slow-paced breathing has the potential to counteract many of the detrimental effects of Covid-19 that can directly affect sports performance. In this paper, we present and justify the use of slow-paced breathing in athletes by focusing on three key outcomes, namely aerobic endurance performance, emotional well-being, and sleep quality. We examine the physiological mechanisms that underpin these three outcomes and review literature showing that slow-paced breathing can activate anti-inflammatory pathways, increase lung capacity and, in turn, improve aerobic endurance, emotional well-being, and sleep quality. We conclude that interventions using slow-paced breathing can have preventive and rehabilitative properties for athletes. Future studies should empirically test the potential of slow-paced breathing to help this specific population.